Energy efficient design in housing of small floor area : appropriateness in housing for the aged - Karol, Elizabeth (Curtin University, 2003)
This thesis seeks to address energy efficient design in a temperate climate in typical small, medium density housing, particularly in housing for the aged. The connections between energy efficient design and small, medium density housing were identified as contemporary issues related to Australian Government policies in two disparate areas. One policy area is reflected in the Government's commitment to assist older people, whether they are active, early retirees or the frail elderly, wealthy or poor, to live in their chosen place of residence. Increasingly this chosen place of residence may be a small, medium density dwelling. The other policy area is that related to reducing energy consumption in buildings. This policy is reflected in recently proclaimed building regulations aimed at reducing space heating/cooling requirements in housing. The building regulations include details of acceptable construction practice for energy efficiency that may not be appropriate in small, medium density housing. It was proposed in this thesis that extensive use of space heating and cooling in housing for the aged was required because well-established benchmarks for energy efficient design in a temperate climate were not generally appropriate in small, medium density dwellings and were particularly inappropriate in housing for the aged. `Appropriate' in this context referred to: indoor temperatures being acceptable without the need for space heating and cooling; retaining the site planning and general form of typical, medium density aged persons housing developments in suburban Australia; cost effectiveness over the life of a building; and fitting the needs of physically and financially vulnerable older people.The methods used to examine the notion of appropriateness commenced with a literature review that related to the general physical and economic status of older people and their needs and responses to space heating and cooling in the home. Further, the literature review considered the principles of energy efficient design and benchmark criteria for energy efficiency. Arising from the literature review, two tools of study were used in order to develop a set of data encapsulating the salient features of small, medium density housing. The first was a multiple case study of typical housing for the aged. This was conceived as a way of determining if small, medium density dwellings could provide appropriate indoor thermal conditions and/or were designed to be energy efficient. The indoor temperatures were monitored in summer and winter and annual energy consumption was established and statistically analysed. The building designs were analysed in terms of their orientation, glazing areas, wall areas, volumes of thermal mass and ventilation capacity and compared with benchmarks for energy efficient design. The second tool involved a series of computer simulations of a typical small, medium density dwelling. The simulation process was utilised to determine if a new set of benchmarks for energy efficient small, medium density dwellings were required that would incorporate the notion of appropriateness. From the multiple case study it was found that, irrespective of design, indoor temperatures in 98% of dwellings were above the acceptable maximum summer temperature of 27.4°C in still air and indoor temperatures in all dwellings were found to be below the acceptable minimum daytime temperature of 19.8°C.The findings also showed that some aspects of the benchmarks for energy efficient design were not appropriate in typical, medium density housing constructed specifically for the aged. From the simulation process it was discovered that acceptable temperatures could be achieved in small medium density housing if the principles of energy efficient design, incorporated within a new set of benchmarks, were integrated with appropriateness criteria for housing for the aged. The approach taken with the new benchmarks was to create both performance based and prescriptive design solutions. The performance model differs from the current benchmarks for energy efficient design in that it establishes key functional objectives for energy efficient design. Compared to the current benchmarks, the prescriptive design solutions show significant reductions in the areas of northerly glazing and total glazing. To compensate for the reduced area of northerly glazing, both direct and indirect means of solar gain are utilised for passive heating. The thesis outcomes have implications for three areas of the construction industry. The prescriptive design solutions presented in building regulations for energy efficiency in housing need to be qualified, the design briefs prepared for energy efficient construction of small, medium density housing need amendment and the approach taken by designers involved in energy efficient small, medium density housing needs to be reconsidered.